Die orthodoxe Wirtschaftspolitik der SPD zwischen 1929 und 1933 - Nikolaus Kowall (Wirtschaftsdienst, 2023)
Die SPD war von 1930 bis 1932 nicht an der Regierung beteiligt, tolerierte aber die Spar- und Deflationspolitik des Kabinetts Brüning. Diese Tolerierung suggeriert, dass die SPD die Regierung Brüning gegen ihre wirtschaftspolitischen Überzeugungen unterstützt hätte, um Demokratie und Frieden zu bewahren. Zumindest im Bereich der Geld- und Fiskalpolitik handelte es sich jedoch eher um Unterstützung als um Duldung. Weite Teile der SPD wandten sich sogar explizit gegen frühe keynesianische Vorstellungen einer aktiven Wirtschaftspolitik. – – The SPD was not part of the government between 1930 and 1932, but tolerated the austerity and deflationary policies of the Brüning cabinet. The term tolerance suggests that the SPD supported the Brüning government against their economic policy convic-tions for the higher purpose of preserving democracy and peace. At least in the area of monetary and fiscal policy, however, it was more a matter of support than tolerance. Significant parts of the SPD even explicitly opposed early Keynesian ideas of an active economic policy. This gave the Nazis, of all people, the opportunity to appropriate an expansive economic policy programme developed by the trade unions and thus ultimately to use it for the labour movement. The zeal with which alternatives to orthodox economic policy were rejected can only be explained by the fact that the austerity and deflationary policies of the Brüning government coincided with the eco-nomic policy ideas and ideological convictions of many social democratic protagonists.
Keywords: B24; N14; N44; 330; Sozialdemokratische Partei; Wirtschaftspolitik; Wirtschaftsgeschichte; Deutschland bis 1945; Sozialdemokratische Partei; Wirtschaftspolitik; Wirtschaftsgeschichte; Deutschland (bis 1945)